Association of Fast‐Food and Full‐Service Restaurant Densities With Mortality From Cardiovascular Disease and Stroke, and the Prevalence of Diabetes Mellitus - Mohsen Mazidi; John R. Speakman (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
BackgroundWe explored whether higher densities of fast‐food restaurants (FFRs) and full‐service restaurants are associated with mortality from cardiovascular disease (CVD) and stroke and the prevalence of type 2 diabetes mellitus (T2D) across the mainland United States. Methods and ResultsIn this cross‐sectional study county‐level data for CVD and stroke mortality, and prevalence of T2D, were combined with per capita densities of FFRs and full‐service restaurants and analyzed using regression. Mortality and diabetes mellitus prevalence were corrected for poverty, ethnicity, education, physical inactivity, and smoking. After adjustment, FFR density was positively associated with CVD (β=1.104, R2=2.3%), stroke (β=0.841, R2=1.4%), and T2D (β=0.578, R2=0.6%) and full‐service restaurant density was positively associated with CVD mortality (β=0.19, R2=0.1%) and negatively related to T2D prevalence (β=−0.25, R2=0.3%). In a multiple regression analysis (FFRs and full‐service restaurants together in same model), only the densities of FFRs were significant (and positive). If we assume these relationships are causal, an impact analysis suggested that opening 10 new FFRs in a county would lead to 1 extra death from CVD every 42 years and 1 extra death from stroke every 55 years. Repeated nationally across all counties, that would be an extra 748 CVD deaths and 567 stroke deaths (and 390 new cases of T2D) over the next 10 years. ConclusionsThese results suggest that an increased density of FFRs is associated with increased risk of death from CVD and stroke and increased T2D prevalence, but the maximal impact (assuming the correlations reflect causality) of each individual FFR is small. Clinical Trial RegistrationURL: http://www.clinicaltrials.gov. Unique identifier: NCT03243253.